MENINGKATKAN KEMAMPUAN BERBICARA ANAK MELALUI METODE BERCERITA DENGAN BONEKA TANGAN PADA ANAK USIA 4-5 TAHUN DI PAUD BALITA BUNDA KECAMATAN TAMBANG KABUPATEN KAMPAR - Siti Aminah; Zulirfan Zulirfan; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in the ability to speak in children age 4-5 years through storytelling with puppets The Center Of Early Childhood Balita Bunda District Regency Of Kampar. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years are numbered 20 children in early childhood Toddler Mother. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that the method of storytelling with hand puppet can improve speech in children aged 4-5 years. It can be seen from the increase in the average percentage of the ability to speak children in the first cycle of 59.79% which is the criterion developing according to expectations (BSH) and an increase of 39.20% in the second cycle be 83.23% which is very good at developing criteria (BSB). So, storytelling with puppets can improve speaking skills of children aged 4-5 years in early childhood Toddler Mother of Mine District of Kampar regency.Keywords : Speech, Storytelling Method, Hand Puppet